1999
DOI: 10.1002/(sici)1098-2337(1999)25:4<269::aid-ab3>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Development of social problem-solving strategies and changes in aggressive behavior: A 7-year follow-up from childhood to late adolescence

Abstract: The aim of this study was to predict a stability of aggressive behavior on the basis of social problem‐solving strategies. Subjects were a total of 120 children, but complete follow‐up data were available only in 47 cases. Their aggressive behaviors were peer rated, and problem‐solving strategies were assessed in childhood subjects being 10 years on average, and 7 years later. Association between a development of social strategies and changes in aggressive behavior was studied with personality‐oriented pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…But it also suggests that, at least at this age, children find it difficult to consider alternative options; that is, to act as social strategists. However, a positive interpretation of this finding would be that there is still room for teaching alternative solutions, especially assertive responses, in order to avoid the development of chronic aggressive behavior [Keltikangas-Ja¨rvinen and Pakaslahti, 1999].…”
Section: Discussionmentioning
confidence: 99%
“…But it also suggests that, at least at this age, children find it difficult to consider alternative options; that is, to act as social strategists. However, a positive interpretation of this finding would be that there is still room for teaching alternative solutions, especially assertive responses, in order to avoid the development of chronic aggressive behavior [Keltikangas-Ja¨rvinen and Pakaslahti, 1999].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, those with low self-efficacy are likely to engage in, among other maladaptive behaviors, bullying and victimization (e.g. Keltikangas-Jarvinen and Pakasiahti 1999).…”
Section: Bullying Victimization and Self-efficacymentioning
confidence: 99%
“…Moreover, the type of processing that occurs during this step depends on one's normative beliefs because the range of behaviors that one thinks are appropriate encompass his/her response selection. Researchers have demonstrated that aggressive children and adolescents are more likely to generate and endorse aggressive problem-solving behaviors as methods they would use to resolve a given situation Erdley and Asher, 1998;Fontaine et al, 2002;Keltikangas-Ja¨rvinen and Pakaslahti, 1999;Richard and Dodge, 1982]. Additionally, results from a longitudinal study provide support for a model where cognitions precede aggressive behavior; the results indicate that response selection processing predicts subsequent aggressive behavior as opposed to aggressive behavior predicting subsequent response selection [Keltikangas-Ja¨rvinen and Pakaslahti, 1999].…”
Section: From Response Selection To Aggressionmentioning
confidence: 99%